SURGICAL TREATMENT OF PHIMOSIS IN DOGS - Correia, Silvia; Jayawardhita, Anak Agung Gde (Buletin Veteriner Udayana, 2023)
Phimosis is a condition in which the male animal cannot remove the penis. This disease can be congenital or acquired. A male dog, mix Kintamani, named Dipo, aged 5 months and weighing 6 kg, has urinating problems. The owner has explained that the case dog cannot urinate like other dogs in general. Clinical examination showed the dog had a small opening (orifice). The hematological examination of the blood showed a decrease in the value of hemoglobin and platelets. The case dog was diagnosed with phimosis with a good ??prognosis. Surgical treatment was performed in the form of enlarging the opening of the sheath (orifice). The premedication used 0.5 ml atropine sulfate subcutaneously with a combination of 0.6 ml of ketamine and 0.6 ml of xylazine anesthesia intravenously. The postoperative treatment used antibiotics of 0.1 ml kg/BW Amoxycilin intravenously on the first day and followed by the antibiotic ointment of 0.1% Gentamicin Sulphate for the suture wound. Anti-inflammatory of 1ml/10kg/BW Tolfenamide acid was injected intramuscularly. The results of surgery and therapy showed that the case dog was comfortable when urinating. The surgical wound has healed on the fifteenth day. It is recommended for owners not to underestimate this condition and to have their animals immediately examined by a veterinarian for further treatment.